Derivatives of 2-aminobenzimidazole potentiate ASIC open state with slow kinetics of activation and desensitization - Evlanenkov, Konstantin K; Komarova, Margarita S; Dron, Mikhail Y; Nikolaev, Maxim V; Zhukovskaya, Olga N; Gurova, Nataliya A; Tikhonov, Denis B (Frontiers in Physiology, 2023)
The pharmacology of acid-sensitive ion channels (ASICs) is diverse, but potent and selective modulators, for instance for ASIC2a, are still lacking. In the present work we studied the effect of five 2-aminobenzimidazole derivatives on native ASICs in rat brain neurons and recombinant receptors expressed in CHO cells using the whole-cell patch clamp method. 2-aminobenzimidazole selectively potentiated ASIC3. Compound Ru-1355 strongly enhanced responses of ASIC2a and caused moderate potentiation of native ASICs and heteromeric ASIC1a/ASIC2a. The most active compound, Ru-1199, caused the strongest potentiation of ASIC2a, but also potentiated native ASICs, ASIC1a and ASIC3. The potentiating effects depended on the pH and was most pronounced with intermediate acidifications. In the presence of high concentrations of Ru-1355 and Ru-1199, the ASIC2a responses were biphasic, the initial transient currents were followed by slow component. These slow additional currents were weakly sensitive to the ASIC pore blocker diminazene. We also found that sustained currents mediated by ASIC2a and ASIC3 are less sensitive to diminazene than the peak currents, suggesting that they are mediated by different open states. According to our results, the main mechanism of action of 2-aminobenzimidazole derivatives is potentiation of this open state with slow kinetics of activation and desensitization.